Positive pole piece, battery and preparation method of positive pole piece
By premixing imidazole ionic liquid into the positive electrode sheet and combining the second electrolyte, the wetting problem caused by the high viscosity of the electrolyte is solved, and the battery performance is improved.
Patent Information
- Application Number
- CN202411916558.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In existing batteries, the high viscosity of imidazole ionic liquid-based electrolytes leads to the inability to completely infiltrate the positive electrode sheet, and there is a risk of liquid leakage in liquid lithium-ion batteries.
By premixing the imidazole ionic liquid into the inside of the positive electrode sheet, and then remaining in the positive electrode sheet after drying, avoiding volatility losses, and combining it with the second electrolyte to form an electrolyte system to solve the infiltration problem.
It realizes rapid and full immersion of the positive electrode sheet, improves the electrochemical performance of the battery, ensures the stability of the battery structure, and improves the first-effect and discharge specific capacity.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a positive electrode sheet, a battery and a preparation method thereof. Background Art
[0002] With the rapid development of new energy technologies, batteries with high safety, high specific energy and low temperature resistance have become an important direction for future development. As a core component in battery manufacturing, the importance and application value of electrolytes are becoming increasingly prominent. However, current ester electrolytes still have problems such as poor low temperature performance, flammability, and difficulty in adapting to high voltage positive electrodes, and liquid lithium-ion batteries have the risk of leakage.
[0003] Ionic liquids are a type of liquid that is completely composed of cations and anions. They can form a variety of compounds through different combinations. Currently, the ionic liquid-based electrolytes used in batteries have a high viscosity problem, which easily leads to the electrolyte not being able to completely infiltrate the positive electrode. In addition, since the infiltration process takes a long time, monomer polymerization is likely to occur during the infiltration process, further deteriorating the wettability. Therefore, the rapid infiltration of the positive electrode by the ionic liquid-based electrolyte becomes the key to improving battery performance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a positive electrode plate, a battery and a method for preparing the same, so as to solve or improve the above-mentioned technical problems.
[0006] The present invention can be implemented like this: In a first aspect, the present invention provides a method for preparing a positive electrode sheet, comprising the following steps: applying a positive electrode slurry containing a positive electrode active material, a binder, a conductive agent, a first solvent and an IL on a current collector, and drying to remove the first solvent; Wherein, IL is an imidazolium ionic liquid; The mass ratio of the positive electrode active material, the binder and the conductive agent is (76~84):(8~12):(8~12); the solid content of the positive electrode slurry is 50%~80%; the amount of IL used is 0.15%~3% of the preset volume of the positive electrode sheet.
[0007] In an optional embodiment, the imidazolium ionic liquid includes at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt; And / or, the positive electrode active material includes at least one of a ternary positive electrode material, a lithium iron phosphate positive electrode material, a lithium manganate positive electrode material and a lithium cobaltate positive electrode material; and / or, the binder comprises polyvinylidene fluoride; and / or, the conductive agent comprises at least one of Super-P, KS-6, conductive graphite, carbon nanotubes, graphene and carbon fiber; And / or, the first solvent includes N-methylpyrrolidone.
[0008] In an optional embodiment, the drying temperature is 60° C. to 90° C., and the drying time is 1 h to 5 h.
[0009] In a second aspect, the present invention provides a positive electrode plate prepared by the preparation method of any one of the aforementioned embodiments.
[0010] In a third aspect, the present invention provides a method for preparing a battery, comprising the following steps: adding a second electrolyte to the positive electrode sheet of the aforementioned embodiment; then adding the first electrolyte, placing a separator, then adding the first electrolyte, placing a negative electrode sheet, standing, packaging, and thermally polymerizing; The first electrolyte includes a monomer, a cross-linking agent, an initiator, an IL and an electrolyte, and the second electrolyte is the first electrolyte without the IL; The first electrolyte contains 10wt%~30wt% of monomer, 10wt%~50wt% of IL and 30wt%~60wt% of electrolyte; the mass ratio of cross-linking agent to monomer is 0.01:1 to 0.05:1, and the mass ratio of initiator to monomer is 0.001:1 to 0.01:1; the electrolyte includes a second solvent, a lithium salt and an additive in a mass ratio of (7.4~8.6):(1~2):(0.4~0.6).
[0011] In an alternative embodiment, the monomer comprises an acrylate monomer; and / or, the cross-linking agent comprises at least one of polyethylene glycol diacrylate and 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane; and / or, the initiator comprises azobisisobutyronitrile; and / or, the second solvent comprises at least one of dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, and at least one of ethylene carbonate and propylene carbonate; and / or, the IL in the first electrolyte comprises an imidazolium-based ionic liquid; and / or, the lithium salt comprises at least one of LiTFSI, LFSI, LiClO4, LiBF4, LIPF6, LiDFOB and LiBOB; And / or, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, and at least one of tris(trimethylsilyl) phosphate and tris(trimethylsilyl) borate.
[0012] In an optional embodiment, the acrylic acid ester monomer includes at least one of butyl acrylate and hexafluorobutyl acrylate; And / or, the imidazolium-based ionic liquid in the first electrolyte includes at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0013] In an optional embodiment, the amount of the second electrolyte added is 18% to 45% of the preset volume of the positive electrode plate; The amount of the first electrolyte added before placing the diaphragm is 5 μL / cm 2 ~10μL / cm 2 , the amount of the first electrolyte added after placing the separator is 5 μL / cm 2 ~10μL / cm 2 .
[0014] In an optional embodiment, the standing time is 0.5h~2h; And / or, the temperature of thermal polymerization is 50° C. to 80° C., and the time of thermal polymerization is 5 h to 10 h.
[0015] In a fourth aspect, the present invention provides a battery, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0016] The beneficial effects of the present invention include: The method provided by the present invention can solve the problem of poor wetting effect of high-viscosity ionic liquid electrolyte on the positive electrode by pre-mixing the imidazole ionic liquid into the interior of the positive electrode plate according to a specific volume. And the above-mentioned imidazole ionic liquid can be effectively stored in the interior of the positive electrode plate during the drying process, and basically no volatilization loss will occur. In addition, the above-mentioned imidazole ionic liquid will not dissolve the binder, which is conducive to ensuring the stability of the positive electrode plate structure. The battery prepared by combining the above-mentioned positive electrode plate with the second electrolyte and the first electrolyte can make the battery have a higher first efficiency and discharge specific capacity. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0018] The positive electrode sheet, battery and preparation method thereof provided by the present invention are described in detail below.
[0019] The present invention provides a method for preparing a positive electrode sheet, comprising the following steps: coating a positive electrode slurry containing a positive electrode active material, a binder, a conductive agent, a first solvent and an IL on a current collector, and drying to remove the first solvent.
[0020] The positive electrode active material may illustratively include at least one of a ternary positive electrode material, a lithium iron phosphate positive electrode material, a lithium manganate positive electrode material, and a lithium cobaltate positive electrode material.
[0021] The binder may include polyvinylidene fluoride (PVDF).
[0022] The conductive agent may include at least one of Super-P, KS-6, conductive graphite, carbon nanotubes, graphene, and carbon fibers.
[0023] The first solvent may include N-methylpyrrolidone (NMP).
[0024] The IL is an imidazole ionic liquid, which may include at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide. The IL will not dissolve the binder PVDF, which is beneficial to ensure the stability of the positive electrode sheet structure.
[0025] If other conventional ionic liquids, such as pyrrolidine ionic liquids, pyridine ionic liquids or quaternary ammonium salt ionic liquids, are used, it is not conducive to broadening the electrochemical stability window of the electrolyte.
[0026] The current collector may illustratively include aluminum foil or the like.
[0027] In the present invention, the mass ratio of the positive electrode active material, the binder and the conductive agent can be (76-84): (8-12): (8-12), such as 76:12:12, 80:10:10 or 84:8:8, etc., or other values within the range of (76-84): (8-12): (8-12). In some typical embodiments, the mass ratio of the positive electrode active material, the binder and the conductive agent is 80:10:10.
[0028] The solid content of the positive electrode slurry may be 50% to 80%, such as 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc., or may be other values within the range of 50% to 80%.
[0029] The amount of IL can be 0.15% to 3% of the preset volume of the positive electrode sheet, such as 0.15%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%, etc., or other values within the range of 0.15% to 3%. In some other embodiments, it can also be added at 1% to 10% of the internal pore volume of the positive electrode sheet, and the internal pore volume of the positive electrode sheet is generally 15% to 30% of the preset volume of the positive electrode sheet.
[0030] If the amount of IL is too little, it will not be conducive to the low-temperature performance; if the amount of IL is too much, it will easily lead to an increase in the electronic conductivity of the electrolyte.
[0031] In some optional embodiments, the drying temperature may be 60°C to 90°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, etc., or other values within the range of 60°C to 90°C.
[0032] The drying time may be 1 h to 5 h, such as 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, etc., or other values within the range of 1 h to 5 h.
[0033] Under the above-mentioned dry conditions, IL can be effectively stored inside the positive electrode plate with little volatilization loss.
[0034] As mentioned above, the present invention can solve the problem of poor wetting effect of high viscosity ionic liquid electrolyte on the positive electrode plate during the later assembly of the battery by pre-mixing a specific ionic liquid into the interior of the positive electrode plate.
[0035] Correspondingly, the present invention provides a positive electrode plate, which is prepared by the above-mentioned preparation method.
[0036] In addition, the present invention also provides a method for preparing a battery, comprising the following steps: adding a second electrolyte to the above-mentioned positive electrode plate; then adding the first electrolyte, placing a separator, adding the first electrolyte again, placing a negative electrode plate, standing, packaging, and thermally polymerizing.
[0037] The first electrolyte includes monomers, crosslinking agents, initiators, IL and electrolyte, and the second electrolyte is the first electrolyte without IL. In other words, it can be understood that the second electrolyte plus the IL pre-mixed into the inside of the positive electrode plate is the first electrolyte.
[0038] In the present invention, the first electrolyte contains 10 wt % to 30 wt % of monomer, 10 wt % to 50 wt % of IL and 30 wt % to 60 wt % of electrolyte.
[0039] In some optional embodiments, the amount of the monomer contained in the first electrolyte may be 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%, etc., or may be other values within the range of 10 wt% to 30 wt%.
[0040] The amount of IL contained in the first electrolyte may be 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt % or 50 wt %, or other values within the range of 10 wt % to 50 wt %.
[0041] The amount of the electrolyte contained in the first electrolyte may be 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt% or 60wt%, etc., or may be other values within the range of 30wt% to 60wt%.
[0042] In some optional embodiments, the mass ratio of the crosslinking agent to the monomer is 0.01:1 to 0.05:1, such as 0.01:1, 0.02:1, 0.03:1, 0.04:1 or 0.05:1, etc., and may also be other values within the range of 0.01:1 to 0.05:1.
[0043] The mass ratio of the initiator to the monomer may be from 0.001:1 to 0.01:1, such as 0.001:1, 0.002:1, 0.005:1, 0.008:1 or 0.01:1, etc., or may be other values within the range of 0.001:1 to 0.01:1.
[0044] In some optional embodiments, the electrolyte may include a second solvent, a lithium salt and an additive in a mass ratio of (7.4~8.6):(1~2):(0.4~0.6). For example, the mass ratio of the second solvent, the lithium salt and the additive in the electrolyte may be 7.4:2:0.6, 8:1.5:0.5 or 8.6:1:0.4, etc.
[0045] In the present invention, the monomer may include an acrylic ester monomer, such as at least one of butyl acrylate and hexafluorobutyl acrylate.
[0046] The cross-linking agent illustratively may include at least one of polyethylene glycol diacrylate (PEGDA) and 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane (OFHDODA).
[0047] The initiator is a thermal initiation type initiator, for example, may include azobisisobutyronitrile (AIBN).
[0048] The second solvent illustratively may include at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), and at least one of ethylene carbonate (EC) and propylene carbonate (PC).
[0049] The IL in the first electrolyte includes an imidazole-based ionic liquid, and its type is the same as that of the IL in the positive electrode plate.
[0050] The lithium salt may illustratively include at least one of LiTFSI, LFSI, LiClO 4 , LiBF 4 , LIPF 6 , LiDFOB, and LiBOB.
[0051] The additive may illustratively include at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), and at least one of tris(trimethylsilyl) phosphate (TMSB) and tris(trimethylsilyl) borate (TMSP).
[0052] In some optional embodiments, the amount of the second electrolyte added is 18% to 45% of the preset volume of the positive electrode plate, such as 18%, 20%, 25%, 30%, 35%, 40% or 45%, etc., and may also be other values within the range of 18% to 45%. In some other embodiments, it may also be added at 1.2 to 1.5 times the internal pore volume of the positive electrode plate, and the internal pore volume of the positive electrode plate is generally 15% to 30% of the preset volume of the positive electrode plate.
[0053] If the amount of the second electrolyte added is too small, it will not be conducive to the full wetting of the positive electrode plate; if the amount of the second electrolyte added is too high, it will interfere with the subsequent addition of the first electrolyte, which is not conducive to maintaining the proportion of the various components of the first electrolyte.
[0054] In some optional embodiments, taking a single-layer battery as an example, the amount of the first electrolyte added before placing the separator is 5 μL / cm 2 ~10μL / cm 2 , such as 5μL / cm 2 , 6μL / cm 2 , 7μL / cm 2 , 8μL / cm 2 , 9μL / cm 2 or 10 μL / cm 2 etc., and can also be 5μL / cm 2 ~10μL / cm 2 The amount of the first electrolyte added after placing the separator can also be 5 μL / cm 2 ~10μL / cm 2 , such as 5μL / cm 2 , 6μL / cm 2, 7μL / cm 2 , 8μL / cm 2 , 9μL / cm 2 or 10 μL / cm 2 etc., and can also be 5μL / cm 2 ~10μL / cm 2 Other values within the range.
[0055] If the amount of the first electrolyte added is too little, it is not conducive to the wetting of the battery separator; if the amount of the first electrolyte added is too much, it will lead to a waste of electrolyte.
[0056] In some optional embodiments, the negative electrode plate may be a negative electrode plate made of lithium metal.
[0057] The separator can be a PE separator coated with 2 μm aluminum oxide on both sides.
[0058] In some optional embodiments, the standing time may be 0.5 h to 2 h, such as 0.5 h, 1 h, 1.5 h or 2 h, etc., or other values within the range of 0.5 h to 2 h. The standing temperature may be room temperature.
[0059] In some optional embodiments, the temperature of thermal polymerization can be 50°C to 80°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, or other values within the range of 50°C to 80°C.
[0060] The time of thermal polymerization can be 5 h to 10 h, such as 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., or other values within the range of 5 h to 10 h.
[0061] It should be noted that other steps in the battery preparation process not described in the present invention can all refer to the prior art and will not be described in detail or limited herein.
[0062] As mentioned above, in the preparation process of the above-mentioned battery, the second electrolyte not containing IL is first added to the positive electrode plate which pre-contains IL. The second electrolyte not containing IL has a lower viscosity and can quickly infiltrate the positive electrode plate and dissolve the IL pre-existing in the positive electrode plate. The dissolved IL and the second electrolyte together form an electrolyte system with the same composition as the first electrolyte. Subsequently, the first electrolyte is added, so that the battery can obtain a better wetting effect under the same wetting system, which is beneficial to improving the electrochemical performance of the battery.
[0063] Correspondingly, the present invention also provides a battery, which is prepared by the above preparation method and has a higher first efficiency and discharge specific capacity.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1 This embodiment provides a battery, and the preparation method thereof is as follows: S1: Prepare the positive electrode sheet.
[0066] The positive electrode slurry containing the positive electrode active material, the binder, the conductive agent, the first solvent and the IL was coated on an aluminum foil, dried at 80° C. for 3 h, and then rolled and cut into pieces to obtain a positive electrode sheet.
[0067] Among them, the positive electrode active material is a nickel-cobalt-manganese ternary positive electrode material, the binder is polyvinylidene fluoride, the conductive agent is Super-P, the first solvent is N-methylpyrrolidone, and the IL is 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt. The mass ratio of the positive electrode active material, the binder and the conductive agent is 80:10:10, the solid content of the positive electrode slurry is 65%, and the amount of IL can be 1% of the preset volume of the positive electrode plate. The volume of the internal pores of the positive electrode plate accounts for 20% of the total volume of the positive electrode plate (the amount of IL is 5% of the internal pore volume of the positive electrode plate).
[0068] S2: Assemble the battery.
[0069] The second electrolyte was dripped onto the positive electrode obtained in S1; then the first electrolyte was dripped, a separator (a PE separator coated with 2 μm aluminum oxide on both sides) was placed, and then the first electrolyte was dripped again, and a lithium metal negative electrode was placed, and the mixture was allowed to stand for 1 hour, packaged, and thermally polymerized at 75°C for 8 hours.
[0070] The first electrolyte contains 20wt% monomer, 10wt% IL and 50wt% electrolyte. The mass ratio of crosslinker to monomer is 0.03:1, and the mass ratio of initiator to monomer is 0.005:1. The electrolyte consists of a second solvent, a lithium salt and an additive in a mass ratio of 8:1.5:0.5.
[0071] The monomer is butyl acrylate, the IL is 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt, the second solvent is obtained by mixing ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, the lithium salt is LIPF6, the additive is obtained by mixing vinylene carbonate and tris(trimethylsilyl)phosphate in a volume ratio of 2:1, the crosslinker is polyethylene glycol diacrylate, and the initiator is azobisisobutyronitrile. The second electrolyte is the first electrolyte without IL.
[0072] The amount of the second electrolyte added is 30% of the preset volume of the positive electrode plate (the amount of the second electrolyte added is 1.5 times the internal pore volume of the positive electrode plate). The amount of the first electrolyte added before placing the diaphragm is 10μL / cm 2 After placing the separator, the amount of the first electrolyte added is also 10 μL / cm 2 .
[0073] Example 2 The difference between this embodiment and embodiment 1 is that the amount of IL contained in the first electrolyte is 20 wt %.
[0074] Example 3 The difference between this embodiment and embodiment 1 is that the amount of IL contained in the first electrolyte is 30 wt %.
[0075] Example 4 The difference between this embodiment and embodiment 1 is that the amount of IL contained in the first electrolyte is 40 wt %.
[0076] Example 5 The difference between this embodiment and embodiment 1 is that the amount of IL contained in the first electrolyte is 50 wt %.
[0077] Example 6 This embodiment provides a battery, and the preparation method thereof is as follows: S1: Prepare the positive electrode sheet.
[0078] The positive electrode slurry containing the positive electrode active material, the binder, the conductive agent, the first solvent and the IL was coated on an aluminum foil, dried at 60° C. for 5 h, and then rolled and cut into pieces to obtain a positive electrode sheet.
[0079] Among them, the positive electrode active material is a nickel-cobalt-manganese ternary positive electrode material, the binder is polyvinylidene fluoride, the conductive agent is Super-P, the first solvent is N-methylpyrrolidone, and the IL is 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt. The mass ratio of the positive electrode active material, the binder and the conductive agent is 76:12:12, the solid content of the positive electrode slurry is 50%, and the amount of IL can be 0.15% of the preset volume of the positive electrode sheet.
[0080] S2: Assemble the battery.
[0081] The second electrolyte was dripped onto the positive electrode obtained in S1; then the first electrolyte was dripped, a separator (a PE separator coated with 2 μm aluminum oxide on both sides) was placed, and then the first electrolyte was dripped again, and a lithium metal negative electrode was placed, and the mixture was allowed to stand for 0.5 h, packaged, and thermally polymerized at 80°C for 8 h.
[0082] The first electrolyte contains 10wt% monomer, 50wt% IL and 40wt% electrolyte. The mass ratio of crosslinker to monomer is 0.01:1, and the mass ratio of initiator to monomer is 0.001:1. The electrolyte consists of the second solvent, lithium salt and additive in a mass ratio of 7.4:2:0.6.
[0083] The monomer is hexafluorobutyl acrylate, the IL is 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt, the second solvent is obtained by mixing propylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1, the lithium salt is LiTFSI, the additive is obtained by mixing fluoroethylene carbonate and tris(trimethylsilyl) borate in a volume ratio of 3:1, the crosslinker is 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, and the initiator is azobisisobutyronitrile. The second electrolyte is the first electrolyte without the IL.
[0084] The amount of the second electrolyte added is 18% of the preset volume of the positive electrode. The amount of the first electrolyte added before placing the separator is 5 μL / cm 2 After placing the separator, the amount of the first electrolyte added is also 5 μL / cm 2 .
[0085] Example 7 This embodiment provides a battery, and the preparation method thereof is as follows: S1: Prepare the positive electrode sheet.
[0086] The positive electrode slurry containing the positive electrode active material, the binder, the conductive agent, the first solvent and the IL was coated on an aluminum foil, dried at 90° C. for 1 h, and then rolled and cut into pieces to obtain a positive electrode sheet.
[0087] Among them, the positive electrode active material is a nickel-cobalt-manganese ternary positive electrode material, the binder is polyvinylidene fluoride, the conductive agent is Super-P, the first solvent is N-methylpyrrolidone, and the IL is 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt. The mass ratio of the positive electrode active material, the binder and the conductive agent is 84:8:8, the solid content of the positive electrode slurry is 80%, and the amount of IL can be 3% of the preset volume of the positive electrode sheet.
[0088] S2: Assemble the battery.
[0089] The second electrolyte was dripped onto the positive electrode obtained in S1; then the first electrolyte was dripped, a diaphragm (a PE diaphragm coated with 2 μm aluminum oxide on both sides) was placed, and then the first electrolyte was dripped again, and a lithium metal negative electrode was placed, and the mixture was allowed to stand for 2 h, packaged, and thermally polymerized at 80 °C for 8 h.
[0090] The first electrolyte contains 30wt% monomer, 10wt% IL and 60wt% electrolyte. The mass ratio of crosslinker to monomer is 0.05:1, and the mass ratio of initiator to monomer is 0.01:1. The electrolyte consists of the second solvent, lithium salt and additives in a mass ratio of 8.6:1:0.4.
[0091] The monomer is butyl acrylate, the IL is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, the second solvent is obtained by mixing ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1.5, the lithium salt is LiBOB, the additive is obtained by mixing vinylene carbonate and tris(trimethylsilyl) borate in a volume ratio of 2:1, the crosslinker is polyethylene glycol diacrylate, and the initiator is azobisisobutyronitrile. The second electrolyte is the first electrolyte without IL.
[0092] The amount of the second electrolyte added is 45% of the preset volume of the positive electrode. The amount of the first electrolyte added before placing the separator is 8 μL / cm 2 After placing the separator, the amount of the first electrolyte added is also 8 μL / cm 2 .
[0093] Comparative Example 1 The difference between this comparative example and Example 1 is that IL is not used in S1; in S2, the first electrolyte is directly added to the positive electrode plate obtained in S1, a separator is placed, and then the first electrolyte is added, and a lithium metal negative electrode plate is placed, and the mixture is allowed to stand for 1 hour, packaged, and thermally polymerized at 80°C for 8 hours.
[0094] Comparative Example 2 The difference between this comparative example and Example 2 is that IL is not used in S1; in S2, the first electrolyte is directly added to the positive electrode plate obtained in S1, a separator is placed, and then the first electrolyte is added, and a lithium metal negative electrode plate is placed, and the mixture is allowed to stand for 1 hour, packaged, and thermally polymerized at 80°C for 8 hours.
[0095] Comparative Example 3 The difference between this comparative example and Example 3 is that IL is not used in S1; in S2, the first electrolyte is directly added to the positive electrode plate obtained in S1, a separator is placed, and then the first electrolyte is added, and a lithium metal negative electrode plate is placed, and the mixture is allowed to stand for 1 hour, packaged, and thermally polymerized at 80°C for 8 hours.
[0096] Comparative Example 4 The difference between this comparative example and Example 4 is that IL is not used in S1; in S2, the first electrolyte is directly added to the positive electrode plate obtained in S1, a separator is placed, and then the first electrolyte is added, and a lithium metal negative electrode plate is placed, and the mixture is allowed to stand for 1 hour, packaged, and thermally polymerized at 80°C for 8 hours.
[0097] Comparative Example 5 The difference between this comparative example and Example 5 is that IL is not used in S1; in S2, the first electrolyte is directly added to the positive electrode plate obtained in S1, a separator is placed, and then the first electrolyte is added, and a lithium metal negative electrode plate is placed, and the mixture is allowed to stand for 1 hour, packaged, and thermally polymerized at 80°C for 8 hours.
[0098] Comparative Example 6 The difference between this comparative example and Example 1 is that an equal amount of N-butylpyridinium tetrafluoroborate is used to replace 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt.
[0099] Comparative Example 7 The difference between this comparative example and Example 1 is that an equal amount of tetramethylammonium tetrafluoroborate is used to replace 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt.
[0100] Comparative Example 8 The difference between this comparative example and Example 1 is that an equal amount of N-butyl-N-methylpiperidinium bromide is used to replace 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide.
[0101] Comparative Example 9 The difference between this comparative example and Example 1 is that the amount of IL used is 0.1% of the preset volume of the positive electrode plate.
[0102] Comparative Example 10 The difference between this comparative example and Example 1 is that the amount of IL used is 5% of the preset volume of the positive electrode plate.
[0103] Test example The batteries obtained in Examples 1-7 and Comparative Examples 1-10 were tested under the conditions of 25° C., 3V-4.3V and 0.1C. The results are shown in Table 1.
[0104] Table 1 Test results
[0105] It can be seen from Table 1 that the battery prepared in the embodiment of the present invention can have a higher first efficiency and discharge specific capacity.
[0106] In summary, the method provided by the present invention can solve the problem of poor wetting effect of high-viscosity ionic liquid electrolyte on the positive electrode by pre-mixing the imidazole ionic liquid into the interior of the positive electrode plate. And the above-mentioned imidazole ionic liquid can be effectively stored inside the positive electrode plate during the drying process, and basically no volatilization loss will occur. In addition, the above-mentioned imidazole ionic liquid will not dissolve the binder polyvinylidene fluoride, which is beneficial to ensure the stability of the positive electrode plate structure. The battery prepared by combining the above-mentioned positive electrode plate with the second electrolyte and the first electrolyte can make the battery have a higher first efficiency and discharge specific capacity.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode sheet, characterized in that: The following steps are involved: Applying a positive electrode slurry containing a positive electrode active material, a binder, a conductive agent, a first solvent and an IL on a current collector, and drying to remove the first solvent; Wherein, the IL is an imidazole ionic liquid; The mass ratio of the positive electrode active material, the binder and the conductive agent is (76~84):(8~12):(8~12); the solid content of the positive electrode slurry is 50%~80%; the amount of the IL is 0.15%~3% of the preset volume of the positive electrode sheet.
2. The preparation method according to claim 1, characterized in that: The imidazole ionic liquid includes at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt; And / or, the positive electrode active material includes at least one of a ternary positive electrode material, a lithium iron phosphate positive electrode material, a lithium manganate positive electrode material and a lithium cobaltate positive electrode material; and / or, the binder comprises polyvinylidene fluoride; and / or, the conductive agent comprises at least one of Super-P, KS-6, conductive graphite, carbon nanotubes, graphene and carbon fiber; And / or, the first solvent comprises N-methylpyrrolidone.
3. The preparation method according to claim 1 or 2, characterized in that: The drying temperature is 60℃~90℃, and the drying time is 1h~5h.
4. A positive electrode sheet, characterized in that: The method is prepared by any one of claims 1 to 3.
5. A method for preparing a battery, characterized in that: The method comprises the following steps: adding a second electrolyte to the positive electrode sheet of claim 4; then adding the first electrolyte, placing a separator, adding the first electrolyte again, placing a negative electrode sheet, standing, packaging, and thermally polymerizing; Wherein, the first electrolyte comprises a monomer, a cross-linking agent, an initiator, an IL and an electrolyte, and the second electrolyte is the first electrolyte without the IL; The first electrolyte contains 10wt%~30wt% of monomer, 10wt%~50wt% of IL and 30wt%~60wt% of electrolyte; the mass ratio of the cross-linking agent to the monomer is 0.01:1 to 0.05:1, and the mass ratio of the initiator to the monomer is 0.001:1 to 0.01:1; the electrolyte includes a second solvent, a lithium salt and an additive in a mass ratio of (7.4~8.6):(1~2):(0.4~0.6).
6. The preparation method according to claim 5, characterized in that: The monomers include acrylic ester monomers; and / or, the cross-linking agent comprises at least one of polyethylene glycol diacrylate and 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane; and / or, the initiator comprises azobisisobutyronitrile; and / or, the second solvent comprises at least one of dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, and at least one of ethylene carbonate and propylene carbonate; and / or, the IL in the first electrolyte comprises an imidazolium-based ionic liquid; and / or, the lithium salt comprises at least one of LiTFSI, LFSI, LiClO4, LiBF4, LIPF6, LiDFOB and LiBOB; And / or, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, and at least one of tris(trimethylsilyl) phosphate and tris(trimethylsilyl) borate.
7. The preparation method according to claim 6, characterized in that: The acrylic acid ester monomer includes at least one of butyl acrylate and hexafluorobutyl acrylate; And / or, the imidazolium-based ionic liquid in the first electrolyte includes at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
8. The preparation method according to claim 5, characterized in that: The amount of the second electrolyte added is 18% to 45% of the preset volume of the positive electrode plate; The amount of the first electrolyte added before placing the diaphragm is 5 μL / cm 2 ~10μL / cm 2 , the amount of the first electrolyte added after placing the separator is 5 μL / cm 2 ~10μL / cm 2 .
9. The preparation method according to claim 5, characterized in that: The standing time is 0.5h~2h; And / or, the temperature of thermal polymerization is 50° C. to 80° C., and the time of thermal polymerization is 5 h to 10 h.
10. A battery, characterized in that: The battery is prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
Air electrode for lithium air cells and preparation method of air electrode
CN103606686A
Ionic-liquid-coated lithium ion battery positive plate as well as preparation method thereof and lithium ion battery
CN104466098A
Electrolyte solution, secondary battery containing electrolyte solution and preparation method therefor
CN109155436A
Method for reducing number of bubbles in process of coating slurry on surface of battery pole piece and application of method in solid electrolyte coating
CN111668455A
Imidazole polyion liquid gel electrolyte and preparation method thereof
CN112185712A